A Review of Employee Retention Strategies in Travel Companies - Bambang Gunarto; Alfath Sandjaya; Willy Arafah; Wahyuningsih Santosa; Agustinus Sri Wahyudi (Indonesian Journal Economic Review (IJER), 2026)
Employee retention presents a significant challenge within human resource management, particularly in the travel industry, characterized by intense competition in the labor market, ongoing digital transformation, and shifting employee expectations. This study aims to analyze and synthesize the existing literature on strategies for employee retention by evaluating the roles of training, reward systems, and work-life balance, as well as their interrelations with work motivation and organizational commitment. A qualitative approach was adopted utilizing a Systematic Literature Review (SLR) methodology. Relevant articles published between 2019 and 2025 were identified, screened, evaluated, and synthesized in accordance with PRISMA guidelines. The findings reveal that competency-based training, equitable reward systems, and effective work-life balance policies are essential strategic practices that enhance employee motivation, bolster organizational commitment, and improve retention rates. Moreover, work motivation and organizational commitment act as critical psychological mechanisms elucidating how strategic human resource management practices influence employees' decisions to remain with an organization. This study proposes a conceptual model that integrates the Resource-Based View (RBV), Strategic Human Resource Management (SHRM), and Social Exchange Theory (SET) to offer a more comprehensive understanding of employee retention within the travel industry. The findings contribute to the advancement of human resource management literature and provide practical insights for organizations aiming to design sustainable employee retention strategies that enhance competitiveness and long-term performance.